2016
DOI: 10.2485/jhtb.25.121
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Capacity of Atrophic Submandibular Gland by Duct Ligation in Mice

Abstract: Function degeneracy of the salivary gland leads to reduced protection against infection and reduced physiological function of the oral cavity, considerably diminishing the patient's quality of life. However, no method of treatment has yet been established to recover the secretory capacity of the salivary gland reduced by the degeneration or disappearance of the gland tissue. Ongoing salivary gland regeneration experiments using cell transplantation aim to introduce clinical regenerative treatment for the saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Histologic findings showed submandibular gland atrophy, disappearance of the acinar portion and an increase in duct-like structures and fibrous connective tissue after 2 months of ligation. These findings were similar to those of short-term ligation studies [1, 2, 31, 32, 35]. Gene expression analysis showed low levels of the acinar cell marker AQP5 [11, 13, 16, 25] and the functional marker α-amylase [11, 36], which is consistent with previous results [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Histologic findings showed submandibular gland atrophy, disappearance of the acinar portion and an increase in duct-like structures and fibrous connective tissue after 2 months of ligation. These findings were similar to those of short-term ligation studies [1, 2, 31, 32, 35]. Gene expression analysis showed low levels of the acinar cell marker AQP5 [11, 13, 16, 25] and the functional marker α-amylase [11, 36], which is consistent with previous results [17].…”
Section: Discussionsupporting
confidence: 91%
“…It is well recognized that the atrophy provoked by obstruction of the salivary ducts induces changes in the structure [ 1 , 2 , 31 , 32 , 35 ], the residual function and the regenerative capacity of the glandular tissue [ 4 , 9 , 19 , 28 ]. Almost all the evidence is based on short-term experiments conducted over approximately 1 week, and there have been no longer-term observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the main duct of the right submandibular gland was ligated for 3 weeks. As presented in the 3W lig group, at the time of the release of ligation, sufficient atrophy of the salivary gland tissues was confirmed by HE and PAS staining, immunostaining for various proteins, and real-time PCR, which was consistent with the report by Akadomari et al 5) . On the other hand, studies on observation after the release of ligation have reported to be of various durations after the release, ranging from 1 week to as long as 2 months 7,8,29) .…”
Section: Discussionsupporting
confidence: 91%
“…Experiments using ligation of salivary glands have been reported to be of various lengths of duration, ranging from 1 week to as long as 3 months [5][6][7][8] . In this study, the main duct of the right submandibular gland was ligated for 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation